Evaluación de la función renal en personas mayores - Oscanoa Espinoza, Teodoro Julio (2025)
Assessing renal function in older adults (OAs) is essential, as it guides the adjustment of geriatric medication dosages, particularly for drugs primarily cleared through the kidneys. Such assessment also enables the diagnosis of chronic kidney disease (CKD), a risk factor for higher rates of hospitalization, cardiovascular events, and mortality. Aging is often accompanied by a reduction in glomerular filtration rate (GFR) ranging from 0.4 to 2.6 mL/min per year; however, this decline is not uniform. Longitudinal studies have shown that in 36 % to 44 % of individuals over 60 years of age, renal function remains relatively stable (1).